Pembuatan Sediaan Oral Nutraceutical dari Ekstrak Gambir - GALUH WIDIYARTI; ANDINI SUNDOWO; MARISSA ANGELINA (Fakultas Farmasi Universitas Pancasila, 2014)
Catechin is one of bioactive compounds in gambier. Result of preliminary studies showed that catechin is active as an antioxidant and antibacterial, thus it was potential as an oral nutraceutical for prevention of dental plaque. In present study, preparation of the oral nutraceutical in the form of mouthwash was performed by variating content of catechin in the extract as formulation parameter. The contents of catechin in the mouthwash solution are 0.01-0.1% (w/v). The mouthwash products were analyzed for pH, antioxidant and antibacterial activities, also particle size. The results showed that mouthwash with catechin content of 0.01-0.08% (w/v) produced the nanoscale of the particle size of mouthwash.